Journalistic practice in times of crisis: A scoping review of role shifts and challenges tied to news production under extraordinary conditions - Lundin Rebecca Bengtsson; Walukiewicz Erika (Nordicom Review, 2025)
This scoping review examines research on journalistic practices in the Nordic countries during societal crises, focusing on how such events disrupt newsroom routines and shape journalistic roles. Mapping the extent and focus of research on crises like the global Covid-19 pandemic, the 2011 Utøya terror attack in Norway, and the Jokela school shooting in Finland, the review identifies key challenges faced by journalists. These include balancing service and watchdog roles, navigating ethical dilemmas, and managing the growing influence of social media. The 32 studies (2007–2024) reveal a modest but growing research focus on journalistic practice during crises in the Nordic region. Findings show that, particularly in the acute phase, journalists prioritise information dissemination over critical scrutiny, often aligning with government messaging. While crises drive technological innovation and accelerate digital adaptation, they also raise ethical challenges, such as how to approach those affected and verify user-generated content. Furthermore, the findings show that the Nordic media systems demonstrated resilience and adaptability during crises.